Early clinical, radiographic and ultrasonographic evaluation of induced osteoarthritis in rabbits treated with autologous platelet concentrate (2018)
The objective of this study was to evaluate, the early effect of the autologous platelet concentrates (APC) on induced osteoarthritis (OA) in the stifle joint through clinical, radiographic and ultrasonographic exams. Fourteen adult males of the New Zealand breed rabbits, with an average body mass of 3.0 kg were used to induce OA in the right hind limb (RHL). Rabbits were randomly divided into two groups, control group and APC group. Animals in the control group received 0.5 ml intra-articular Ringer Lactate solution. Immediately after the repair of the cranial cruciate ligament, the APC group received 0.5 ml APC intra-articular injections whose mean concentration of platelets was1.8 times the basal levels. Intra-articular injections were applied immediately after joint stabilization. Rabbits treated with APC showed significantly better clinical scores (p<0.05) when compared with rabbits in the control group in relation to pain sensitivity, joint effusion presence and limb support 15 days after APC application (M3). The range of limb motion showed statistically significant difference (p<0.05) in flexion and extension of RHL in M3 in both groups. The radiographic and ultrassonographic images showed the presence of degenerative joint process in both groups without statistical difference between them. From the results it can be concluded that APC has a beneficial clinical effect in joints affected by OA, favoring the use of the limb and controlling pain sensitivity, and that radiography and ultrasonography images are successful tools in the evaluation of the progression of OA.